DUTIES AND LEGAL RESPONSIBILITIES OF PHARMACISTS IN PHARMACEUTICAL - Ady Supryadi (Universitas Muhammadiyah Mataram, 2023)
Pharmacist as a professional health worker in the field of pharmacy services in carrying out its duties is based on the code of Ethics as a moral psychiatric profession work. But a profession code of ethics is sometimes not very much noticed. Consequently, the hallmark of the noble profession of pharmacy as a provision of assistance in the form of drug services oriented to community needs, wear off and tend to be commercial transactions of pharmaceutical products that are business - oriented. The research method uses a normative juridical approach with research specifications of the analytical descriptive.Data collection is conducted through the inventory and study of primary, secondary, and tertiary legal materials which are then analyzed in a qualitative juridical. The duty and authority of the pharmacist in carrying out the work of the pharmacy is in the manufacture including the quality control of pharmaceutical preparations, securing, procurement, storage and distribution of drugs, drug management, medical treatment of Doctor's prescription, drug information services, and the development of medicines, medicinal materials and traditional medicines. The responsibility of the pharmacist in the drug service prescribed by the Doctor is to prioritize the needs and safety of patients. The overall responsibility of pharmacists in drug service is pharmaceutical care to improve the quality of patient life